PAIN MEDICATION USE AMONG CROHN'S DISEASE AND ULCERATIVE COLITIS PATIENTS BEFORE AND AFTER INITIATION OF BIOLOGIC THERAPY. (21st January 2021) - Hunter, Theresa; Naegeli, April; Nguyen, Chi; Shan, Mingyang; Smith, Joseph; Tan, Hiangkiat; Gottlieb, Klaus; Isenberg, Keith
Abstract: Objective: The purpose of this analysis was to describe pain medication utilization of newly diagnosed patients with Crohn's disease (CD) and ulcerative colitis (UC) over 12-months before and after initiation of a biologic. Methods: This is a retrospective study using administrative claims from the HealthCore Integrated Research Database. Patients newly diagnosed with CD or UC who initiated a biologic from 1/1/2014 to 7/31/2017 were included. Medications that could be used for pain control were assessed 12-months prior and 12-months after biologic initiation. Demographics, baseline clinical characteristics, and pain medication use were described using descriptive statistics. Frequencies and percentages were provided for categorical variables and means, standard deviations, and medians were presented for continuous measures. The differences in pain medication use 12 months prior and 12 months after biologic initiation were assessed using McNemar's Test for categorical variables and Wilcoxon signed-rank test for continuous variables.. Results: 540 CD patients and 373 UC patients were included in this analysis. CD patients had a mean age of 36.8 years, 50.0% were female, and the mean time from diagnosis to biologic initiation was 7.1 months. UC patients had a mean age of 39.9 years, 44.0% were female, and the mean time from diagnosis to biologic initiation was 10.9 months. Prior to biologic initiation, 23.1% of CD patients were prescribed NSAIDs, 78.1% glucocorticoids, 49.4% opioids, and 29.3% neuromodulators. Similarly, prior to biologic initiation, 20.9% of UC patients were receiving NSAIDs, 91.4% glucocorticoids, 40.8% opioids, and 29.5% neuromodulators. Twelve months after biologic initiation, use of NSAIDs (CD: 23.1% vs. 15.0%; UC: 20.9% vs. 15.8%) and glucocorticoids (CD: 78.1% vs. 58.9%; UC: 91.4% vs. 74.3%) significantly decreased among CD and UC patients. Opioid use decreased among UC and CD patients; however this decrease was only statistically significant for CD patients (CD: 49.4% vs. 41.5%; UC: 40.8% vs. 36.5%). Use of neuromodulators significantly increased during 12-months after biologic initiation compared to 12 months prior to initiation among CD (29.3% vs. 33.7%) and UC (29.5% vs. 35.7%) patients. Conclusion: Use of pain medications such as NSAIDs, glucocorticoids, opioids, and neuromodulators were common among CD and UC patients. Though rates of NSAIDs and glucocorticoids decreased after the initiation of biologics, 59% of CD and 74% of UC patients were still receiving glucocorticoids, and 15% of CD and 16% of UC patients were still receiving NSAIDs 12-months after initiation of a biologic. In addition, 42% of CD and 37% UC patients were still receiving opioids 12-months after initiation of a biologic. The results suggested that CD and UC patients are still receiving pain medication even after initiating biologics.